Overview of the future impact of wearables and artificial intelligence in healthcare workflows and technology - Perry A. LaBoone; Oge Marques (International Journal of Information Management Data Insights)
Technological advancements have had a significant impact on healthcare throughout history, leading to improved quality of care and greater efficiency, which ultimately benefits patients. The use of wearables and artificial intelligence (AI) in the healthcare industry has the potential to continue this trend. Wearables and AI enable real-time and continuous monitoring of a patient’s medical health information, which helps physicians detect diseases early and monitor patients during their recovery. However, there are challenges in managing the large amounts of data generated by these technologies and integrating them into existing electronic health records (EHRs). Despite these challenges, the introduction of AI promises to revolutionize the healthcare industry, much like the industrial and digital revolutions of the past. This paper will explore the transformative role of wearables and AI technology in healthcare, assess how it will change fundamental workflows, and highlight how AI solutions will become ubiquitous and expected by patients.